2014
DOI: 10.1007/s00774-014-0574-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of bisphosphonate on osteoclast function contributes to improved skeletal pain in ovariectomized mice

Abstract: The aim of this study was to evaluate skeletal pain associated with osteoporosis and to examine the inhibitory effect of bisphosphonate (BP) on pain in an ovariectomized (OVX) mouse model. We evaluated skeletal pain in OVX mice through an examination of pain-like behavior as well as immunohistochemical findings. In addition, we assessed the effects of alendronate (ALN), a potent osteoclast inhibitor, on those parameters. The OVX mice showed a decrease in the pain threshold value, and an increase in the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 41 publications
1
42
1
Order By: Relevance
“…Chronic bisphosphonate administration also reverses bone loss and reduces cutaneous referred pain in the early stages of the pathology (i.e., 6–8 weeks after ovariectomy) in rodent models of ovariectomy-induced osteoporosis [5]. Therefore, we tested the efficacy of bisphosphonate therapy in mice with chronic, fully established osteoporosis, 6 months after ovariectomy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic bisphosphonate administration also reverses bone loss and reduces cutaneous referred pain in the early stages of the pathology (i.e., 6–8 weeks after ovariectomy) in rodent models of ovariectomy-induced osteoporosis [5]. Therefore, we tested the efficacy of bisphosphonate therapy in mice with chronic, fully established osteoporosis, 6 months after ovariectomy.…”
Section: Resultsmentioning
confidence: 99%
“…One important observation in this study was that the decreased BMD and significant pain hypersensitivity were maintained for 6 months in OVX mice. Only a few previous studies have followed the long-term course of pain sensitivity in OVX rats [32] or mice [5, 33, 34]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporotic osteoclasts degrade bone minerals by secreting protons through the vacuolar H + -ATPase, creating local acidic microenvironments by inflammation 49,50) , which should evoke the stimulation of TRPV1. Furthermore, this acidic microenvironment produced by inflammation stimulates acid-sensing ion channels (ASICs) in acid-sensing nociceptors 51,52) . These stimulations evoked by osteoporotic osteoclasts lead to the chronic increased expression of inflammatory pain-related neuropeptides, calcitonin gene-related peptides (CGRP), and DRG neurons, innervating osteoporotic vertebrae 39) .…”
Section: The Mechanism Of Osteoporotic Painmentioning
confidence: 99%
“…A bisphosphonate has effects on other molecules too. Alendronate improves osteoporotic pain by inhibiting TRPV1 52) . In addition, a randomized, controlled trial showed that alendronate produced a stronger analgesic effect than calcitonin in postmenopausal osteoporotic women 64) .…”
Section: Antiresorptive Agents: Bisphosphonate and Denosumabmentioning
confidence: 99%